1990
DOI: 10.1177/030089169007600313
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Stage IV Ovarian Carcinoma Treated with Platinum-Based Regimens

Abstract: Eight factors were analyzed for prognostic significance in univariate analyses in a series of 76 women with stage IV ovarian carcinoma treated with combination chemotherapies including cisplatin or carboplatin. The clinical objective and pathologic complete response rates were 51.2% and 27.3%, respectively. Median overall survival and progression-free survival were 15 and 7 months, respectively. No variables reached statistical significance. Trends toward better survival were noted for grades 1 and 2 for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…abdomen or lower abdomen vs both) in stage IIIB-IIIC disease was associated with poor OS.Few studies have investigated the impact of residual disease after primary debulking surgery on OS in women diagnosed with stage IV EOC. Smaller series have been published on stage IV disease [6][7][8][9][10]15. In line with previous studies 11,14 our results confirm that residual disease = 0 after primary debulking surgery is one of the most powerful determinants of OS in stage IV disease.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…abdomen or lower abdomen vs both) in stage IIIB-IIIC disease was associated with poor OS.Few studies have investigated the impact of residual disease after primary debulking surgery on OS in women diagnosed with stage IV EOC. Smaller series have been published on stage IV disease [6][7][8][9][10]15. In line with previous studies 11,14 our results confirm that residual disease = 0 after primary debulking surgery is one of the most powerful determinants of OS in stage IV disease.…”
supporting
confidence: 91%
“…Smaller series have been published on stage IV disease. [6][7][8][9][10]15 Recently, the first larger study on the influence of residual disease on outcomes in 573 women with stage IV EOC was published. They found that residual disease = 0 was associated with a significantly improved outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations